Changing the Game in Science and Mathematics Higher Education : Final Report. - Johnson, Elizabeth (Office for Learning and Teaching, 2014)
Final report of a Teaching Fellowship at La Trobe University. This report describes the construction of the ACDS Teaching and Learning Centre (ACDS TL Centre), a new national initiative in the learning and teaching of science and mathematics in Australian universities. The fellowship designed the ACDS TL Centre with the active participation of leaders of learning and teaching in science and mathematics from Australian universities.